Impact of European chemicals regulation on the industrial use of plasticizers and patterns of substitution in Scandinavia. (October 2018) - Sackmann, Kathrin; Reemtsma, Thorsten; Rahmberg, Magnus; Bunke, Dirk
Abstract: REACH aims at promoting the safe use of chemicals in Europe, inter alia by identification and regulation of substances of very high concern (SVHCs). Once identified, SVHCs need to be substituted by safer alternatives. However, substitutes are frequently not safer than the substances that they replace but rather show similar hazard profiles, resulting in regrettable substitution. This paper investigates the impact of chemicals regulation on substitution of chemicals by analyzing time trends in the industrial use of chemicals from 2000 to 2014 in Scandinavia. It is shown that the use of ten water-relevant SVHCs decreased by about 90% in the considered period in Sweden as compared to a control group of unregulated substances which decreased by only 20%. A closer inspection of the use of 23 highly used plasticizers revealed that the use of regulated phthalate plasticizers decreased while the use of non-phthalate plasticizers increased. A first comparison of hazardous properties showed that during the 15-years period chemical substitution drastically reduced the chemical hazard burden of plasticizers in Scandinavia for both, the environment and human health. This study shows that regulation and the related discussion on chemicals safety have significantly reduced the chemical hazard burden from plasticizers in Scandinavia since the year 2000. It is assumed that similar trends can be found for the whole European Union. To combat regrettable substitution, mitigation options are suggested, including information-based tools for the identification of safer alternatives and an improved accessibility of information on production volumes and uses of chemicals to allow for an improved assessment of chemical's risk. Graphical abstract: Highlights: Regulation decreased the use of substances of very high concern in Sweden. Regulated phthalate plasticizers were mostly substituted by non-phthalate plasticizers. Regrettable substitution could be identified at an early stage. Despite regrettable substitution, human health and environmental hazards decreased.